Análisis del impacto producido por la utilización del acero reciclado en la construcción de edificaciones en la ciudad de Barranquilla (2018)
The construction of any type of civil work is a process that requires the perfect harmony of each of its phases to be successful, no doubt, the calculation of quantities and selection of materials to be used in one of the most representative phases due to its importance in determining the quality of the work in general, highlighting steel as one of the most commonly used materials in any work. The recycling of materials is a practice that has been gaining strength over the years, to represent for projects a decrease in costs and work execution times, among many other benefits. This projects carries out a detailed analysis of the ways in which society, the environment and the economy are impacted by the implementation of recycled steel use practices in the construction of buildings in the city of Barranquilla, in order to qualify them and quantify them according to a scale of viability established by the judgment of subjective logic, so that one can be certain of the favorability of this practice for the world of construction and can recommend and promote its implementation in projects.